Análise da segurança hídrica pela abordagem Nexus água, energia e alimento com uso de tecnologias sociais. Estudo de caso: município de Paragominas, estado do Pará - Bueno, Lívia Vitória França (Universidade Federal de São Carlos, 2025)
Water security has become one of the main challenges for sustainable development, especially in territories that face deficiencies in basic infrastructure, such as sanitation, regular access to drinking water and energy, in addition to the low presence of effective public policies, a common reality in many rural communities in the eastern Amazon. This study aimed to analyze water security in Paragominas (PA) through the Water, Energy and Food Nexus approach, evaluating the applicability of social technologies as sustainable solutions, based on technical and socio-environmental criteria obtained from the literature, classifying them according to their suitability for rural, urban or mixed contexts. The methodology adopted consisted of a bibliographic review of technical studies, manuals and scientific articles, with the organization of information in analytical tables, application of Nexus criteria for sectoral evaluation and preparation of a final summary table. Ten social technologies were analyzed, including dry toilets, solar water pumping, biodigester septic tanks and mini-cisterns. It is concluded that the integration between social technologies and the Nexus AEA approach contributes significantly to local water security, offering viable solutions for promoting sustainability, social inclusion and community autonomy in regions with greater lack of infrastructure.
Analysis of water security through the water, energy and food Nexus approach using social technologies. Case study: municipality of Paragominas, state of Pará
Keywords: Segurança da água; Sustentabilidade; Amazônia Oriental; Área rural; Área urbana; ENGENHARIAS::ENGENHARIA SANITARIA